Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Terhadap Kemampuan Berpikir Kritis Siswa SMP pada Materi Tata Surya - Sri Wahyuni*; Zainur Rasyid Ridlo; Dwi Nova Rina (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Articulate Storyline is software that can be used as a presentation media or communication tool. This interactive media does not require any programming knowledge during the creation process, because all animations can be created using the "Trigger" option, making it easier for teachers to create interactive materials. This research aims to develop an interactive learning media based on articulate storyline on the material of the solar system in junior high school. The development model used is the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The development of this media also aims to see the level of effectiveness of interactive learning media based on articulate storyline on the critical thinking skills of grade VII A students at SMPN 1 Sukapura. The indicator of Facione's critical thinking ability used by researchers. The results of the development obtained a validation of 89.9% which was included in the very valid category. The results of the implementation of interactive learning media based on Articulate Storyline is 96.5% which shows that interactive learning media based on Articulate Storyline is very practical. The average N-gain result of 0.6 interactive learning media based on Articulate storyline can improve the critical thinking skills of junior high school students on the solar system material and is included in the medium category. And the average student response is 94% which shows that the interactive learning media based on Articulate Storyline has a positive response